Increased muscle expression of interleukin-17 in Duchenne muscular dystrophy - Loredana De Pasquale; Adele D’Amico; Margherita Verardo; Stefania Petrini; Enrico Bertini; Fabrizio De Benedetti (2012)
Duchenne muscular dystrophy (DMD) is a degenerative muscle wasting disease caused by mutations in the dystrophin gene. Dystrophic muscle is characterized by chronic inflammation, and inflammatory mediators could be promising targets for innovative therapeutic interventions. We analyzed muscle biopsy samples of DMD-affected children to characterize interleukin (IL)-17 and Forkhead box P3 (Foxp3) expression levels and to identify possible correlations with clinical status.Expression levels of IL-17, Foxp3, tumor necrosis factor-α (TNF-α), monocyte chemoattractant protein-1 (MCP-1), IL-6, and transforming growth factor-β (TGF-β) were analyzed by real-time PCR in muscle biopsy samples from patients with DMD (n = 27) and juvenile dermatomyositis (JDM) (n = 8). Motor outcome of patients with DMD was evaluated by North Star Ambulatory Assessment score.In DMD, we found higher levels of IL-17 and lower levels of Foxp3 mRNA compared with those for a typical inflammatory myopathy, JDM. Moreover, the IL-17/Foxp3 ratio was higher in DMD than in JDM biopsy samples. IL-17 mRNA levels appeared to be related to the expression levels of other proinflammatory cytokines (TNF-α and MCP-1) and significantly associated with clinical outcome of patients.The association of IL-17 expression with levels of other inflammatory cytokines and with the clinical course of DMD suggests a possible pathogenic role of IL-17.